The Effect of Quality Costs on Operating Profit - Osi Luthviani Putri; Mulyanah Mulyanah; Anistya Vinta Desi (Pascasarjana Universitas Sultan Ageng Tirtayas, 2026)
This study aims to investigate the influence of each component of quality costs on a company’s ability to generate operating profit. A quantitative research design was employed, targeting a foreign direct investment (FDI) manufacturing company located in the Balaraja industrial area. A total of 36 respondents were selected using purposive sampling. Data were analyzed using Structural Equation Modeling (SEM) with the assistance of SmartPLS software. The empirical results indicate that preventive costs do not have a significant effect on operating profit, while assessment costs, internal failure costs, and external failure costs exhibit a significant and positive impact on operating profit..